Strategi Pemberdayaan Masyarakat dalam Pengelolaan Lingkungan Berkelanjutan melalui Program Desa Peduli Lingkungan Darat di Kelurahan Semolowaru, Kota Surabaya - Gyska Indah Harya; Sabrina Dinda Kharisma Putri; Ahmad Ghilbran Rosyadi; Priscillia Stevanies Nicander Putri; Marcellino Azhar Kartiko (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Sustainable environmental management is an important challenge in the midst of climate change and rapid urbanization. Rapid urbanization growth has posed challenges related to the availability of food and green space in urban areas. This community service activity aims to empower the community in maintaining and preserving the environment through a series of educational activities related to hydroponic technology and verticulture as an alternative solution to urban agriculture and the Clean Friday action in Semolovaru Village. The main activities include hydroponic socialization, cultivation practices with hyoponic and verticulture systems and the Clean Friday program. The methods used include mediation and training, among others. Seeing the general situation in Semolowaru village where there is no land for cultivation accompanied by settlements that are classified as densely populated, it is very suitable for the implementation of urban farming. The purpose of urban farming itself is to realize the harmony, coolness, and beauty of the dominant urban area with various buildings and public facilities as well as dense residential areas. Furthermore, in community service activities, clean Friday activities are carried out which aim to improve the cleanliness and comfort of the village hall area, build community awareness, strengthen the relationship between the village government and residents, and encourage active participation in community activities.